Critical Review on Hotel Tax over Boarding House from the Perspective of Islamic Equality Principle - Khoirul Hidayah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2017)
Perception of community are the regulation about tax of hotel in boarding house over 10 (ten) rooms in The Law No. 28 of 2009 about The Region Tax and Retribution is unclear and unfair. The problems are what are the nature meaning of hotel and boarding house services, second, analize tax of hotel in boarding house by fairness perspective. The research method is normative research with modern interpretation and fairness theory. The result are the nature meaning of hotel and boarding house services are differences. The regulation about tax of hotel in boarding house over 10 (ten) rooms is unfair.